Penguatan Pelayanan Berbasis Konsep Hijau: Studi Kasus Bamboo Cafe Penglipuran sebagai Model Layanan Berkelanjutan - I Gusti Ayu Melistyari Dewi (Journal of Innovative and Creativity, 2025)
This research analyzes the strengthening of green-based service at Bamboo Cafe Penglipuran as a sustainable model for nature-based hospitality businesses. The study applies a descriptive qualitative approach through field observation, semi-structured interviews, document analysis, and the researcher's experience as excellent service trainer for the entire staff. Data is analyzed using Miles & Huberman's interactive model comprising data reduction, data display, and conclusion drawing. Results show that attitude, effective communication, and service consistency drive synergy of green concept with service excellence, yielding holistic and sustainable visitor experiences that prioritize both comfort and environmental sustainability. Bamboo Cafe can be a reference for eco-hospitality F&B in natural tourism destinations and contributes to the development of sustainable hospitality practices in Indonesia.